STABILITY OF GRAPHENE SURFACE AN APPLICATION OF CHIRAL MODEL - Y.P. RYBAKOV; A.B. AHMED; J. SAMBO; MAGAJI, ABDULKADIR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
A suspended sheet of pure graphene a layer of carbon atoms bonded together in a honeycomb lattice is the most two-dimensional system imaginable. Graphene sheet have for long been known to exist in disguised from graphite (stacked graphene layers) it was generally believed that an extended graphene sheet would not be stable against the effect of thermal and other fluctuations. Furthermore, it was believed that even if they were stable, it would be impossible to isolate them so that their properties could be studied systematically. Based on this the chiral model was suggested, the ideal graphene plane were determined by the kink-like solution. The corrugation of the graphene surface was described in the form of ripple and rings. Thus, our graphene plane reviles the tendency of bending.